Admission and discharge criteria for adolescents requiring inpatient or residential mental health care: a scoping review. Issue 2 (19th February 2020) - Evans, Nicola; Edwards, Deborah; Carrier, Judith
ABSTRACT: Objective: This scoping review sought to locate and describe criteria relating to admission to and discharge from inpatient mental health care for adolescents aged 11 to 19 years in the literature. Introduction: In the United Kingdom (UK) and internationally, it is estimated that one in 10 children and adolescents has a diagnosable mental health problem. Children and adolescents with the highest levels of need are cared for in hospital, but there is a high demand for beds and a general lack of agreement regarding the criteria for admission to, and discharge from, such units. Inclusion criteria: We considered research studies that focused on criteria for admission to and discharge from inpatient mental healthcare units for adolescents aged 11 to 19 years. We included all quantitative and qualitative research designs and text and opinion papers. Methods: We searched MEDLINE, Embase, PsycINFO, CINAHL, ERIC, British Nursing Index, Applied Social Sciences Index and Abstracts, ProQuest Dissertations and Theses, the Cochrane Central Register of Controlled Trials, OpenGrey, EThOS and websites of professional organizations for English language citations from 2009 to February 2018. Potentially relevant citations were retrieved in full and their citation details imported into the JBI System for the Unified Management, Assessment and Review of Information. Full texts of selected citations were assessed in detail against the inclusion criteria by two independent reviewers. Findings were extracted directly into tables accompanied by a narrative summary relating to the review objectives. Results: Thirty-five citations were included: quantitative research studies (n = 18), qualitative research studies (n = 1), and textual and opinion publications (n = 16). Of the quantitative research studies, 16 used a retrospective cohort design using case note reviews and two were prospective cohort studies. The qualitative study used interviews. The research studies were conducted in nine countries: USA (n = 7), UK (n = 3), New Zealand (n = 2), Israel (n = 2), Canada (n = 1), Norway (n = 1), Ireland (n = 1), Greece (n = 1) and Turkey (n = 1). The 16 textual and opinion publications included book chapters (n = 3), reviews (n = 3), policy and guidance documents (n = 3), reports (n = 3) and service specifications (n = 4). The majority of these were published in the UK (n = 10), with the remainder published in Ireland (n = 2), Australia (n = 2), and USA (n = 2). Research was conducted across a variety of settings including child and adolescent mental health service inpatient and outpatient units, emergency departments and adult psychiatric units. Length of stay, where recorded, ranged from < 1 day to 351 days. Several categories emerged from the data: type of admission process, referral or point of access, reasons for admission to inpatient mental health care, assessment processes, criteria for discharge and reasons for non-admission. Conclusion: There is little evidence identifying which behavioral or symptomatic indicators suggest that admission is required, beyond retrospective identification of diagnoses attributed to adolescents who become inpatients. The threshold of severity of risk or need is not currently articulated. No studies were identified that drew on the perspectives of adolescents and their families or carers regarding criteria warranting admission to inpatient mental health care, which indicates an important area for future investigation.